Platelet-rich plasma-enhanced “plum blossom” bone grafting for refractory femoral nonunion: a single-center study of 33 cases - Chen, Jianrong; Wang, Shiheng; Zhou, Huolong; Feng, Zhoulian; Ma, Zhiliang; Wang, Kunyu; Kang, Yuwen (Frontiers in Bioengineering and Biotechnology, 2026)
BackgroundRevision surgery for femoral nonunion is technically challenging, and there is limited evidence supporting effective treatments for cases with multiple failed revisions. This study aims to evaluate the efficacy of platelet-rich plasma-enhanced “plum blossom” bone grafting combined with a bioactive chamber in treating refractory femoral nonunion after multiple failed revisions.MethodsA retrospective analysis was conducted on patients with refractory femoral nonunion treated at a high-level trauma center between January 2021 and July 2024. These patients underwent mechanical optimization, platelet-rich plasma -enhanced “plum blossom” autologous iliac bone grafting, and bioactive chamber therapy. Radiographic outcomes included union rate and limb shortening, while clinical outcomes encompassed healing time, visual analog scale pain score, SF-36 quality of life score, Harris hip score, and complications.ResultsThirty-three patients were included (24 males, 9 females), with a mean age of 42.64 ± 13.03 years. The average number of previous surgeries was 2.64 ± 1.17. The nonunion types were hypertrophic (4 cases, 12.10%), atrophic (24 cases, 72.70%), and oligotrophic (5 cases, 15.20%). The mean bone defect was 3.87 ± 1.05 cm, and the mean follow-up duration was 16.06 ± 3.37 months. The union rate was 96.97% (32/33), with a mean healing time of 9.78 ± 1.75 months. Post-treatment, significant improvements were observed in VAS score (4.27 ± 1.18 vs. 1.21 ± 1.05, p < 0.001), Harris hip score (50.91 ± 8.47 vs. 86.39 ± 7.75, p < 0.001), SF-36 score (59.21 ± 5.63 vs. 84.48 ± 5.32, p < 0.001), and limb shortening (2.20 ± 0.64 vs. 0.32 ± 0.57, p < 0.001). Two patients (6.06%) experienced severe complications (1 case of persistent nonunion, 1 case of deep vein thrombosis).ConclusionThe synergistic effect of biomechanical stability and biological stimulation is a critical pathway to overcoming traditional treatment limitations. This study provides a reference method for managing refractory and recalcitrant femoral nonunion.